2016
DOI: 10.1016/j.tplants.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for High-Throughput Stress Phenotyping in Plants

Abstract: Advances in automated and high-throughput imaging technologies have resulted in a deluge of high-resolution images and sensor data of plants. However, extracting patterns and features from this large corpus of data requires the use of machine learning (ML) tools to enable data assimilation and feature identification for stress phenotyping. Four stages of the decision cycle in plant stress phenotyping and plant breeding activities where different ML approaches can be deployed are (i) identification, (ii) classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
515
0
16

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 803 publications
(532 citation statements)
references
References 74 publications
1
515
0
16
Order By: Relevance
“…The author uses the HOG and SVM classifier algorithms [12]. Arti Singh, Baskar Ganapathysubramanian, Asheesh Kumar Singh, Soumik sarkar, describes the various methods about plant phenotyping and how the leaf images are extracted by using various machine learning and data mining techniques [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The author uses the HOG and SVM classifier algorithms [12]. Arti Singh, Baskar Ganapathysubramanian, Asheesh Kumar Singh, Soumik sarkar, describes the various methods about plant phenotyping and how the leaf images are extracted by using various machine learning and data mining techniques [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…
We found the article by Singh et al [1] extremely interesting since it introduces and showcases the utility of machine learning for high throughput data-driven plant phenotyping.With this letter we want to emphasize the role that image analysis and processing have in the phenotyping pipeline beyond what [1] suggests, both in analyzing phenotyping data (e.g., to measure growth) but also when providing effective feature extraction to be used by machine learning. Key recent reviews have shown that it is image analysis itself (what the authors of [1] consider as part of pre-processing) that has brought a renaissance in phenotyping [2].
…”
mentioning
confidence: 99%
“…We found the article by Singh et al [1] extremely interesting since it introduces and showcases the utility of machine learning for high throughput data-driven plant phenotyping.…”
mentioning
confidence: 99%
See 2 more Smart Citations